2010
DOI: 10.1016/j.jadohealth.2009.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Waist-to-Height Changes During Teen Years in Girls Are Influenced by Childhood Body Mass Index

Abstract: Purpose This study examined longitudinal changes in waist-to-height ratio and components of BMI among black and white females. Methods Girls were recruited at age 9 through the NHLBI Growth and Health Study (NGHS), and followed annually over ten years. Girls were grouped into low (<20th %tile), middle, and high (>80th %tile) BMI on the basis of race-specific BMI percentile rankings at age 9, and low, middle, and high waist-to-height ratio, on the basis of waist-to-height ratio at age 11. BMI was partitioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Furthermore, longitudinal data on BMI tracking from more than 80,000 children and adolescents included within this study cohort (of whom 9848 were moderately obese and 4295 severely obese at the index visit) demonstrate that severely obese children tend to maintain the same degree of obesity over time, particularly when evident at a young age. These findings support data from other longitudinal pediatric cohorts documenting a strong tracking effect of elevated BMI in childhood, as well as into adulthood [18-23]. Similar shifts in BMI across normal, overweight, obese and severely obese categories were also observed in a multisite school-based study of 3993 U.S. sixth graders re-examined later in eigth grade, where 76% of severely obese youths (alternatively defined by the 99 th BMI percentile) remained severely obese after 2.5 years of follow-up [24].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, longitudinal data on BMI tracking from more than 80,000 children and adolescents included within this study cohort (of whom 9848 were moderately obese and 4295 severely obese at the index visit) demonstrate that severely obese children tend to maintain the same degree of obesity over time, particularly when evident at a young age. These findings support data from other longitudinal pediatric cohorts documenting a strong tracking effect of elevated BMI in childhood, as well as into adulthood [18-23]. Similar shifts in BMI across normal, overweight, obese and severely obese categories were also observed in a multisite school-based study of 3993 U.S. sixth graders re-examined later in eigth grade, where 76% of severely obese youths (alternatively defined by the 99 th BMI percentile) remained severely obese after 2.5 years of follow-up [24].…”
Section: Discussionsupporting
confidence: 89%
“…Puberty is associated with increases in lean body mass as well as fat mass, with a greater increase in fat mass in girls compared with boys (49). Girls experience a greater increase in fat mass throughout childhood and puberty than boys, and heavier girls experience a greater increase in fat mass during puberty than other girls (50)(51)(52)(53). There is a rise in insulin resistance during puberty (54,55), as well as a worsening of various components of the metabolic syndrome, and concurrently, changes in leptin and adiponectin (56)(57)(58).…”
Section: Effect Of Childhood and Adolescent Obesitymentioning
confidence: 99%
“…A US study found that higher BMI and increased weight gain during childhood lead to greater waist-to-height ratio and elevated BMI during teenage years. The most evident increase in fat mass was observed after pubertal growth spurt and in black race [14]. Another study using data from 1999 Health Survey for England found that teenage girls from Afro-Carribbean and South-Asian background are at increased risk of being obese when compared with general population [15].…”
Section: Introductionmentioning
confidence: 99%
“…risk of neonatal mortality [62] risk of birth defects [63,64] risk of obesity [35,65] risk of giving birth to LGA infant [66] risk of LGA and macrosomia [14,57,67] age of menarche [38] risk of type 2 diabetes [35] risk of metabolic syndrome [65,68,69] Overweight adolescents may be a particularly vulnerable group in terms of experiencing unfavourable pregnancy outcomes such as gestational diabetes [16], pre-eclampsia [17], caesarean delivery and delivering infants with macrosomia [18]. Interestingly, findings from a recent UK study found that higher levels of gestational weight gain may go some way towards supporting fetal growth when the teenagers themselves are growing, although 'excess' weight may contribute to weight retention and long-term obesity.…”
Section: Introductionmentioning
confidence: 99%